Engineering elastic bioactive composite hydrogels for promoting osteogenic differentiation of embryonic mesenchymal stem cells - Wang, Min; Guo, Yi; Deng, Zexing; Xu, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
The development of bioactive materials with good mechanical properties and promotion of stem cell osteogenic differentiation has important application prospects in bone tissue engineering. In this paper, we designed a novel organic‒inorganic composite hydrogel (FPIGP@BGN-Sr) utilizing diacrylated F127 (DA-PF127), β-glycerophosphate-modified polyitaconate (PIGP) and strontium-doped bioactive glass nanoparticles (BGN-Sr) through free radical polymerization and coordination interactions and then evaluated its promoting effect on the osteogenic differentiation of mouse embryonic mesenchymal stem cells in detail. The results showed that the FPIGP@BGN-Sr hydrogel exhibited a controlled storage modulus by changing the amount of BGN-Sr. Notably, the FPIGP@BGN-Sr hydrogel possessed excellent elastic ability with a compressive strain of up to 98.6% and negligible change in mechanical properties after 10 cycles of compression. In addition, the FPIGP@BGN-Sr hydrogel had good cytocompatibility, maintained the activity and proliferation of mouse embryonic mesenchymal stem cells (C3H10T1/2), and effectively enhanced the activity of alkaline phosphatase, osteogenic gene expression and biomineralization ability of the cells. In conclusion, the excellent mechanical properties and osteogenic biological activity of the FPIGP@BGN-Sr hydrogel make it a promising organic‒inorganic composite bioactive material for stem cell-based bone regeneration.